Innovative Technologies Used to Increase the Effectiveness of Foreign Language Teaching - Ravshanova Nasiba Karamatovna (Researchparks Publishing, 2022)
This article focuses on the desire of teachers for innovation, their search, application in education, the development of skills, competencies, the ability to continuously work on themselves, innovation, advanced pedagogical technologies, an interactive environment, it is believed that students become the driving force behind the learning process, which, ensures the quality and efficiency of education.